Study of The Conformation Changes of Blood Serum - P. Vidyarthi, R.; Kumar, Amrendra; Chaurasia, Jageshwar; Chaurasia, Arunchal (Asian Journal of Chemistry, 2010)
pH and conductometric titration of blood serum (Goat's) in 5% aqueous medium gave two inflexions and the corresponding two breaks with N/20 HCI and only one inflexionlbreak with N/20 NaOH solution. In 0.25 M KCI there was only one inflexion in both acid and alkali. In 8 M urea solution the number of inflexionlbreaks rose to three. The coulombic interactions between oppositely charged sities in the protein chain seems to have screened, at least in part by a neutral salt like KCI present in large concentration as also shown by the fact that the fall of pH by the addition of (5 mL) of acid is more in aqueous medium than in KCI solution. Urea being a powerful disruptor of hydrogen bond the protein chain would, in all probability, exist as a random coil conformation and the study of pH titration curves revealed the acidic and basic groups having three step reactions in it. The nature of the titration curve is also altered in urea solution. The initial pH of blood serum rose from 7.2 to 7.9 showing there by the protons of the NH3 cations in the zwitter ions be irnmobilised by hydrogen bond formation with urea as suggested by Donovan, Laskowski and Scherage. Expansion of the protein random coil in the denatured form also seems to occur in the pH titration.